2004
DOI: 10.1364/opex.12.004001
|View full text |Cite
|
Sign up to set email alerts
|

Stationary optical wave fields with arbitrary longitudinal shape by superposing equal frequency Bessel beams: Frozen Waves

Abstract: -In this paper it is shown how one can use Bessel beams to obtain a stationary localized wavefield with high transverse localization, and whose longitudinal intensity pattern can assume any desired shape within a chosen interval 0 ≤ z ≤ L of the propagation axis. This intensity envelope remains static, i.e., with velocity v = 0; and because of this we call "Frozen Waves" such news solutions to the wave equations (and, in particular, to the Maxwell equations). These solutions can be used in many different and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
175
0
17

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 181 publications
(196 citation statements)
references
References 5 publications
4
175
0
17
Order By: Relevance
“…The problem was already solved by us and the method developed for the particular case of lossless media [12,13], i.e., when n I = 0 → β Im = 0. For those cases, it was shown that the choice…”
Section: The Mathematical Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The problem was already solved by us and the method developed for the particular case of lossless media [12,13], i.e., when n I = 0 → β Im = 0. For those cases, it was shown that the choice…”
Section: The Mathematical Methodologymentioning
confidence: 99%
“…The method is a generalization of a previous one [12,13] and consists in the superposition of Bessel beams in (7), the real and imaginary parts of their longitudinal wave numbers being given by Eqs. (5)and (8) happily enough, this condition is satisfied in a great number of situations.…”
Section: The Mathematical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…This intensity envelope remains static, i.e., has velocity v = 0; and because of this in a previous paper [6] we have called "Frozen Waves" (FW) these new solutions to the wave equations (and, in particular, to the Maxwell equations). Inside the envelope of a FW only the carrier wave does propagate: And the longitudinal shape, within the interval 0 ≤ z ≤ L, can be chosen in such a way that no nonnegligible field exists outside the pre-determined high-intensity region.…”
Section: Introductionmentioning
confidence: 99%